Oligomeric Proanthocyanidins Counteracts the Negative Effects of High Level of Dietary Histamine on American Eel (Anguilla rostrata) - Zhai, Shaowei; Wang, Yue; He, Yingxia; Chen, Xuehao (Frontiers in Marine Science, 2020)
The economic loss of intestinal inflammation by histamine in diet has caused concern in eel culture; it is urgent to develop a natural feed additive to alleviate the negative effects of high-level dietary histamine. Oligomeric proanthocyanidins (OPCs), as the natural antioxidant to scavenge free radicals, were supplemented to alleviate the effects of dietary histamine on parameters of growth, serum biochemistry, and liver metabolites of juvenile American eels in the present study. Juvenile American eels with an initial body weight of 10.84 ± 0.16 g per fish were divided into a control group fed commercial diet, a HIS group fed commercial diet supplemented 300 mg/kg histamine, and an OPC group fed commercial diet supplemented 300 mg/kg histamine and 300 mg/kg OPC. The trial period was 11 weeks. Compared with the HIS group, the OPC group showed that dietary OPC supplementation could alleviate growth retardation; decrease activities of glutamic-pyruvic transaminase, glutamic-oxaloacetic transaminase, acid phosphatase, and alkaline phosphatase; and lower levels of immunoglobulin and complement 3 in serum. With the upregulation of L-cysteine and dihydrouracil involving cysteine and methionine metabolism, beta-alanine metabolism, sulfur metabolism, pantothenate and CoA biosynthesis, and pyrimidine metabolism in the liver, OPC supplementation could alleviate the effects of high-level dietary histamine on growth and serum biochemical parameters. There were no significant differences of growth performance and serum biochemical parameters between the HIS group and control group. These results indicated that OPC might act as a potential feed additive to effectively counteract the negative effects of dietary histamine on juvenile American eel.